Practicing Teachers’ Attributions for the Behaviour of Students With Learning Disabilities and Attention-Deficit/Hyperactivity Disorder - Frohlich, Jona R; Goegan, Lauren D; Daniels, Lia M (Alberta Journal of Educational Research, 2020)
More students with attention-deficit/hyperactivity disorder (ADHD) and learning disabilities (LD) are being taught within the regular education classroom than ever before even though children with these disorders often require additional educational supports. Therefore, it is critical that teachers understand the challenges experienced by these students, as well as feel efficacious when it comes to teaching and supporting them. Attribution theory is a widely used theoretical framework by which to explain teachers’ cognitions. We surveyed 151 practicing teachers and asked them to respond to items related to attributions for students’ behaviour and their teaching self-efficacy. First, we examined teachers’ perceptions of the primary cause of the difficulties experienced by students qualitatively. We open-coded responses and three major themes emerged: biology/genetics, the environment, and skill deficits. These themes differed somewhat depending on whether the student had ADHD or LD. Second, we examined the relationship between teachers’ attributions for student behaviours and their sense of teaching self-efficacy quantitatively. For students with ADHD, controllable attributions predicted teachers’ self-efficacy (β = .30, p = .005). For students with LD, controllable and internal attributions predicted teacher self-efficacy (β = .34, p = .001, β = .24, p = .009, respectively). Third, we examined the results of both analyses simultaneously to determine areas of convergence and divergence with respect to attribution theory. The results have implications for both teachers and students (e.g., attributional interventions designed to foster a sense of self-efficacy), as well as provide directions for future research and teacher training. Keywords: ADHD, LD, practicing teachers, attributions, self-efficacy, mixed-methods Le nombre d’élèves atteints du trouble du déficit de l'attention avec ou sans hyperactivité (TDAH) ou des troubles d’apprentissage (TA) sont intégrés plus que jamais aux classes ordinaires, même si les enfants affectés par ce type de difficultés ont souvent besoin d’un soutien éducationnel supplémentaire. Il est donc critique que les enseignants comprennent les défis que vivent ces élèves et que les enseignants se sentent efficaces dans l’enseignement et l’appui qu’ils leur apportent. La théorie attributive est un cadre théorique dont l’emploi est répandu pour expliquer les cognitions des enseignants. Au cours d’une enquête auprès de 151 enseignants en exercice, nous les avons interrogés au sujet des attributions relatives au comportement des élèves et de leur sentiment d’efficacité personnelle en enseignement. Nous avons d’abord étudié, qualitativement, les perceptions des enseignants quant à la première cause des difficultés que vivent les élèves. Trois thèmes majeurs se sont dégagés des réponses aux questions ouvertes : la biologie/la génétique, l’environnement et des lacunes sur le plan des habiletés. Ces thèmes variaient quelque peu selon que l’élève était atteint du TDAH ou des TA. Deuxièmement, nous avons étudié, quantitativement, le rapport entre les attributions des enseignants relatives au comportement des élèves et leur sentiment d’efficacité personnelle en enseignement. Par rapport aux élèves atteints du TDAH, les attributions contrôlables étaient prédictives du sentiment d’efficacité personnelle chez les enseignants (β = .30, p = .005). Relativement aux élèves atteints des TA, les attributions contrôlables et internes étaient prédictives du sentiment d’efficacité personnelle chez les enseignants (β = .34, p = .001, β = .24, p = .009, respectivement). En troisième lieu, nous avons étudié les résultats des deux analyses simultanément afin de déterminer les points de convergence et de divergence par rapport à la théorie attributive. Les résultats ont des retombées tant pour les enseignants que les élèves (par ex. des interventions attributionnelles conçues pour favoriser un sentiment d’efficacité personnelle) et ils proposent de nouvelles orientations en matière de recherche et formation des enseignants. Mots clés : TDAH, TA, enseignants en exercice, attributions, efficacité personnelle, méthodes mixtes